2012
DOI: 10.1093/annonc/mdr511
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine late sequelae in long-term survivors of childhood non-Hodgkin lymphoma

Abstract: Background: Aim of this study was to investigate the long-term endocrine effects of treatment of childhood non-Hodgkin lymphoma (NHL). Patients and methods:A single-center cohort of 84 survivors (22 females) was included in this retrospective study.Median age was 21 years (9-40 years) and time after cessation of therapy 12 years (4-30 years). Height, weight, percentage fat, lean body mass (LBM), bone mineral content (BMC), bone mineral density of total body (BMD TB ) and bone mineral density of lumbar spine (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 55 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…One previous prospective study assessed the association between pre‐diagnosis IGF‐I and risk of MM and found no significant association 11. In the few clinical and retrospective studies of the IGF axis in relation to lymphoma, circulating IGF‐I concentrations have been found variously to be low in 84 survivors of childhood NHL,17 to not differ at diagnosis between 57 MM patients and 20 controls,9 and to be related to prognosis for MM patients (with low serum IGF‐I at diagnosis being associated with favourable prognosis) 18. A recent study in classical HL patients has shown that despite the oncogenic effect of IGF‐IR, a higher expression at diagnosis predicted a favourable outcome both for overall survival and 5‐year progression‐free survival 19.…”
Section: Discussionmentioning
confidence: 99%
“…One previous prospective study assessed the association between pre‐diagnosis IGF‐I and risk of MM and found no significant association 11. In the few clinical and retrospective studies of the IGF axis in relation to lymphoma, circulating IGF‐I concentrations have been found variously to be low in 84 survivors of childhood NHL,17 to not differ at diagnosis between 57 MM patients and 20 controls,9 and to be related to prognosis for MM patients (with low serum IGF‐I at diagnosis being associated with favourable prognosis) 18. A recent study in classical HL patients has shown that despite the oncogenic effect of IGF‐IR, a higher expression at diagnosis predicted a favourable outcome both for overall survival and 5‐year progression‐free survival 19.…”
Section: Discussionmentioning
confidence: 99%
“…However, BMI assesses weight relative to height, and does not differentiate between muscle, fat, or bone 11 . Accordingly, BMI may not be the best measure of obesity among CCS as many survivors are of short stature 12 or have reduced bone 13, 14 and muscle mass 15, 16 . In fact, in a study that compared survivors of acute lymphoblastic leukemia (ALL) to age- and sex-matched controls, BMI was not found to differ between survivors and controls, even though survivors had higher body fat percentages than controls as determined by DXA 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Over 40% of bone mass is obtained during puberty, and over 90% of the total adult bone mass is acquired by the end of puberty . Peak bone mass is an important determinant of future bone health . Thus, elucidating the bone health status at the end of pubertal development (∼16 years old for both sexes) is critical for assessing future bone health.…”
Section: Introductionmentioning
confidence: 99%
“…Bone health has previously been examined in adolescent and young adult cancer survivors. RFs for BMD deficits were elucidated through these important studies, and management plans for the future were developed . However, these studies primarily involved small cohorts (approximately 30–50 young survivors) and only one or two disease types (primarily leukemia and lymphoma).…”
Section: Introductionmentioning
confidence: 99%